Separation of nadolol racemates by high pH reversed-phase preparative fixed-bed chromatography: comparison of C18 materials - Arafah, Rami (2018)
Fixed-Bed technology will be used for the multicomponent preparative separation of a pharmaceutical beta-blocker chiral drug. New strategies using different achiral stationary phases will be presented. Nadolol is a quaternary mixture of equal amounts of four stereoisomers and will be used as case-study. A new methodology for the design, optimization and experimental implementation of the multicomponent separation will be introduced, including the use of three different achiral adsorbents, the screening and choice of the best adsorbent-solvent combination, taking in account the final preparative separation using the fixed-bed technology. Extensive experimental and simulation results will be presented, including solvent screening, measurement of equilibrium adsorption isotherms, breakthrough measurements, and fixed-bed (Azura prep HPLC unit) experimental preparative separation using C18 columns under reversed-phase mode.